Timely post-discharge medication reviews to Improve Continuity—the Transitions Of Care stewardship (TIC TOC) study in rural and regional Australia: a parallel-group randomised controlled trial study protocol - Sepehr Shakib; Manya Angley; Jonathan Penm; Charley Budgeon; Kim Nguyen; Rebekah Jane Moles; Faye McMillan; Rohan A Elliott; Paul Yates; Katie Phillips; Jenny Chen; Stephen Ross Carter; et al. (BMJ Open)
Introduction Transition of care from hospital is a period when the risks of medication errors and adverse events are high, with 50% of adults discharged having at least one medication-related problem. Pharmacist-led medication reviews can reduce medication errors and unplanned readmission when completed promptly post-discharge; however, they are underutilised. A Transition of Care Stewardship pharmacist has been proposed to facilitate and coordinate a patient’s discharge process and facilitate a timely post-discharge medication review. Access to pharmacist medication review in rural and regional areas can be limited. This protocol describes a randomised controlled trial (RCT) to determine whether a virtual Transition of Care Stewardship pharmacist reduces medication-related harm in rural and regional Australia.Method and analysis Multicentre RCT involving patients at high risk of medication-related harm discharged from regional and rural hospitals to a domiciliary residence. Eligible patients must be aged≥18 years, admitted under a medical specialty, be discharged to a domiciliary setting, have a regular general practitioner (GP) or be willing to visit a GP or an Aboriginal Medical Service after discharge for medical follow-up, have a Medicare card and be at high risk of readmission. High risk of readmission is defined as either a previous admission to the hospital or Emergency Department (ED) presentation in the past 6 months AND≥three regular medications OR on at least ONE high-risk medication. A total of 922 participants will be recruited into the study. Enrolled participants will be randomised to the intervention or control (usual care). The intervention will include a virtual Transition Of Care Stewardship pharmacist to ensure that patients receive discharge medication reconciliation, medication counselling, medication list and communicate directly with primary care providers to facilitate a timely post-discharge medication review. Usual care will include informing the patient’s clinical inpatient treating team that the patient is at high risk of medication misadventure and may benefit from a post-discharge Home Medicines Review (a GP-referred pharmacist medication review funded by the Australian Government).Data analysis will be performed on a modified intent-to-treat basis. The primary outcome assessed is a composite of a first unplanned medication-related hospitalisation or ED presentation within 30 days of hospital discharge. Comparisons between the intervention and usual care groups for the primary outcome will be made using a mixed-effects logistic regression model, adjusting for site-level clustering as a random effect.Ethics and dissemination This study is approved to be conducted at the Western New South Wales Local Health District via the Research Ethics and Governance Information System (approval number: 2023/ETH00978). To ensure the needs of Aboriginal and Torres Strait Islander patients are appropriately addressed, ethics for this study were submitted and approved by the Aboriginal Health and Medical Research Council (approval number: 2148/23). Manuscripts resulting from this trial will be submitted to peer-reviewed journals. Results may also be disseminated at scientific conferences and meetings with key stakeholders.Trial registration number ACTRN12623000727640.